Mitos Dan Oposisi Biner Dalam Novel Puya Ke Puya Karya Faisal Oddang: Antropologi Levi Strauss - Rapi, Muhammad; Ridwan, Ridwan; Rasding, Reski Fajria (TITIK DUA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2025)
This study aims to analyse cultural structures in novels using Lévi-Strauss's structural anthropology theory, particularly the concept of binary oppositions such as life versus death, tradition versus modernity, and social obligations versus individual freedom. Using qualitative descriptive research methods, the analysis shows that tradition in this novel is not merely a tradition, but also a structure of thinking that is inherited and continuously negotiated. The results of the study show that custom and culture have an influence on an individual's personal life, as well as how social status can be influenced by custom and culture. The results also reveal several binary oppositions, ranging from the relationship between life and death, as well as custom and modernisation. Thus, this novel illustrates how culture is not static but continues to evolve within social dynamics.